Adaptive attenuation of virulence mediated by Wzc mutation in ST11-KL47 Carbapenem-resistant Klebsiella pneumonia - Yufeng Dai; Yufeng Dai; Qiang Zhao; Huanhuan Yan; Huanhuan Yan; Kun Ye; Lifeng Wang; Ling Guo; Na Guo; Na Guo; Wenwen Li; Wenwen Li; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionThe impact of the hypermucoviscosity (HMV) phenotype in ST11-KL47 carbapenem-resistant Klebsiella pneumoniae (CRKp) pathogenicity warrants investigation for public health risk assessment.MethodsWe analyzed 230 clinical ST11-KL47 CRKp to identify the key factor in mucoviscosity acquisition via comparative genomic analysis. Sedimentation value served as the objective index to quantify HMV. The virulence in vivo was assessed using Galleria mellonella and mouse infection models. We employed genome engineering, capsular polysaccharides (CPS) quantification, and visualization to explore the role of Wzc mutation in CPS biosynthesis and HMV. The biological impact of Wzc-mediated HMV was investigated through competitive growth analysis, biofilm formation, serum resistance, anti-phagocytic ability, and adhesion assays. Transcriptomic analysis and scanning electron microscopy (SEM) were utilized to explore the relationship between polysaccharide composition, physical distribution, and changes in virulence.ResultsThe Wzc mutations are identified as the key to mucoviscosity acquisition. Unexpectedly, Wzc-mediated HMV CRKp exhibits reduced pathogenicity versus non-mucoviscosity (NMV) strains in different animal models, with competitive disadvantage, decreased biofilm formation, serum resistance, and adhesion, yet higher anti-phagocytic ability in vitro. CPS extraction and visualization of genome-engineered strains verify the Wzc mutations mediate HMV by standardizing CPS chain length and overproducing cell-free extracellular polysaccharides (cell-free EPS). Transcriptomic results, lipopolysaccharides (LPS) quantification, and SEM collectively indicate a downregulation of LPS synthesis and the masking of LPS in HMV strains.DiscussionThese findings demonstrate that the Wzc-induced HMV attenuates ST11-KL47 CRKp virulence by modifying the exopolysaccharide composition and physical distribution.